Gross Morphometric Studies on Thyroid and Adrenal Glands of Jaffarabadi Buffalo during Different Seasons of the Year - Sharma, Anil (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on thyroid and adrenal glands of Jaffarabadi buffaloes to evaluate the changes in gross morphology and biometry during winter, summer, and rainy seasons. The samples were collected from ten adult Jaffarabadi buffaloes during each season. The topographic position, shape, and color of the thyroid and adrenal glands did not show any distinguishable differences during different seasons; however, the consistency of thyroid was slightly harder during rainy and summer seasons as compared to thewinter season. The thyroid gland revealed a significant increase in weight and volume during winter and rainy seasons as compared to the summer season. The length of the thyroid did not show any significant changes during seasons, whereas width is significantly more during the rainy season and thickness is lowest during summer. The left adrenal gland is flat and ‘C’ shaped with slightly spongy consistency whereas the right adrenal is ‘V’ or ‘Y’ shaped with a comparatively hard consistency. Weight, volume, length and thickness of both left and right adrenals were highest during the rainy season and lowest during the winter season.